Rozwój nauczania akademickiego w zakresie dyscyplin handlowych w Poznaniu - Gałecki, Ryszard (Wydział Prawa i Administracji UAM, 1980)
Higher education in the scope of commerce possesses more than 50-years long tradition in Poznan. The field and programmes of teaching were subjected to different transformations. Guiding subjects served only as a supplement at the beginning to the main purpose of studies, which was a general economic education, Education of businessmen was of a very narrow, specialists character at first in the post-war period (f. ex. purchasing agricultural products), but later on it turned to broader education with possibilities of choice of a narrower specialization in commerce or services. The evolution of academic teaching in the sphere of commerce in Poznan is inseparable connected with Professor Zbigniew Zakrzewski. To Him, above all, education of a large group of scientists in the sphere of commodity turnover at the Poznań School of Economics can be indebted. Some Professor Zakrzewski's alumni reinforced other academic centres in Poland.
The Evolution of Academic Teaching in the Scope of Commercial Disciplines in Poznań